Investigating simplified fixed bed design models for the adsorption of fluoride onto crushed burnt clay pot - Mehari, Beraki Bahre; Mayabi, Alfred O.; K. Kakoi, Beatrice (International Journal of Engineering and Technology, 2014)
The breakthrough curves of fluoride adsorption onto crushed burnt clay pot in mini column fixed bed depths of 15, 20, and 25 cm at a continuous flow rate of 2.5, 5, 10 and 15 ml/min were used to investigate the simplified fixed bed design models (BDST and EBRT). The influent fluoride concentration was 5 mg/L and the breakthrough point was taken at 30% of the influent concentration. Results indicate that the BDST curve had the form of straight line explaining more than 99.6% of the data and thus confirmed to obey the BDST model. For the same operating parameters of 50 cm bed depth and 36 cm/h flow rate, 350 L water could have been defluoridated using BDST model, however, in the case of the pilot experiment, 324 L were defluoridated from 5 to 1.5 mg/L fluoride. This was 8% higher only and hence was not significant. Similarly, when the bed depth data were analyzed, results indicate that at higher EBRT values, the adsorbent exhaustion rate were similar to the batch adsorption and thus the EBRT model could be used to optimize for the design of defluoridation unit. Therefore, the simplified fixed bed design models (BDST and EBRT) could be successfully applied to analyze the column performance and design a fluoride adsorption system based on crushed burnt clay pot as a sorbent media.